New graphic design : the 100 best contemporary graphic designers - Fiell, Charlotte; Fiell, Peter; Heller, Steven (London : Goodman Fiell, 2013)
A thought provoking round-up of today's most interesting visual communication projects, 'New Graphic Design' surveys the very latest work from 100 of the world's most exciting and groundbreaking practitioners.
boek
Keywords: Graphic artists; Graphic arts